Product Innovation, Digital Marketing, and Marketing Performance of Halal Culinary: The Moderating Role of Regulation - Raihanah Daulay; Muhammad Ramadhan; Muhammad Ridwan (International Journal of Business Economics (IJBE), 2025)
Purpose – This research aims to formulate the factors that influence the marketing performance of halal culinary SMEs in North SumatraMethodology – This research adopts an explanatory research approach, which  describes the cause-and-effect relationships between the research variables and the hypothesis testing. The research was conducted in North Sumatra. Data was collected by distributing questionnaires to respondents through Google Forms using the WhatsApp application to 385 MSME business actors. The data analysis method used SEM (Structural Equation Modeling) assisted by the smartpls4 (Partial Least Squares) program to determine the relationship between manifest variables as indicators and latent variables, thus providing meaning to those relationshipsFindings – Findings in product innovation research provide a significant impact on marketing performance. Digital marketing has a significant impact on the marketing performance of halal food in SMEs. Regulations have a strong influence on marketing performance but have a weak influence on digital marketing.Originality/Novelty – The performance of halal culinary marketing is influenced by product innovation and digital marketing. Regulations have a strong impact on the product innovation variable and a weak impact on the digital marketing variable.Implications – SMEs must have the ability to develop product innovations in order to compete in the market and utilize social media more effectively and efficiently, as well as take advantage of government-established programs to develop their business.